PEMBUATAN BIOPLASTIK BERBAHAN DASAR PATI KULIT PISANG KEPOK/SELULOSA SERBUK KAYU GERGAJI - Elisusanti; Muhammad Nur Alam; Ilmiati Illing (Universitas Cokroaminoto Palopo, 2019)
Bioplastic was synthesized from starch as a result of the extract from Kepok banana peel and added with cellulose as the result of isolation of sawdust as a filler. Bioplastic mixture is added with glycerol as a plasticizer. Making bioplastics was done by the sol-gel method at a temperature of 90 oC for 1 hour from forming the sol to a bioplastic gel. Cellulose filler material varied from 0, 2, 4, and 6% w / v. The results of biodegradation testing show that bioplastics with the addition of cellulose have a higher rate of degradation than bioplastics without cellulose. Bioplastics with the highest degradation rates were obtained at cellulose addition of 2% w / v which reached degradation up to 100% for 15 days of burial. The phenomenon of bioplastic degradation is evidenced by the results of FTIR characterization which shows that bioplastic samples with cellulose additions have decreased very sharply at several peak absorption after burial. This also occurs in bioplastics without cellulose, but the decrease in peak absorption intensity is no more significant than bioplastics with cellulose addition.